Pengaruh Presentase Kuning Telur Itik dan Asam Formiat Dalam Proses Peminyakan terhadap Kekuatan Fisik Kulit Ayam Pedaging Samak Khrom (Jurnal Ilmu dan Teknologi Hasil Ternak, 2017)
The purpose of this study was to find out the effect of ducks yolk and formic acid in fat liquoring process of the tanned skin.  The materials used in this study were 30 pieces of 7 weeks of broiler chicken shank. The study was carried out using completely randomized design. The variables measured were softness, tensile strength and stretch of the tanned skin. Data were analyzed by analysis of variance and followed by Duncan’s Multiple Range Test. The research results showed that the addition of ducks yolk and formic acid didn’t gave significantly affect on the softness (p>0.05), while gave highly significant affect on tensile strength and stretch (p<0.01). Interaction between two treatment didn’t gave significantly affect (p>0.05) on the softness and stretch, and have significantly (p<0.05) on the tensile strength of leather. The conclusion of this research the addition of 11% duck yolk and 1% formic acid in fat liquoring is the best treatment for broiler chicken shank chrome tanning on the skin softness (2,667), tensile strength (135,707 kg/cm2), and stretch (37,34%), respectively.